Pemberdayaan BUMDes dalam Mendukung Pembangunan Berkelanjutan Berdasarkan Maqashid Al-Shari’ah di Provinsi Jawa Timur: Empowerment of BUMDes in Supporting Sustainable Development Based on Maqashid Al-Shari'ah in East Java Province (Al Dzahab, 2025)
Purpose: To analyze the existence of BUMDes for sustainable development based on maqasid al-shari’ah in East Java.Design/methodology/approach: This study uses a qualitative research approach with a literature review method. Data sources were taken from 5 samples of BUMDes empowerment in East Java sourced from Journals.Findings: Based of the 5 samples used, the implementation of BUMDes in East Java, has supported the SDGs in the areas of zero poverty, zero hunger, gender equality, decent work and economic growth, responsible consumption and production, and partnership for the goals, which align with the 5 fundamental elements of maqasid al-shari’ah, namely hifz al-din, hifz al-nafs, hifz al-nasl, hifz al-aql, and hifz al-mal.Research implications: The empowerment of BUMDes in East Java is implemented in the form of establishing various business units in different field, ranging from MSMEs shops, land utilization for agriculture, livestock, and fisheries, rental business, sharia financing business, and training programs that can ebhance human resources.